PENGARUH GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. PLAMBO PRATAMA JOYO SANTOSO DI KOTA TEGAL - Slamet Nasroni (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2016)
ABSTRACT In the era of increasingly fierce globalization of competition within companies,companies need to pay attention to human resources in order to be able tocompete competitively. This study aims to find out: (1) Does salary affect employee performance, (2)Does the incentive affect employee performance, (3) Do salaries and incentivesjointly affect employee performance. The type of research used in this study uses a quantitative approach that is ex post facto, which is to study the facts that already exist. The process is in the form of describing by interpreting the data that has been processed from 40 employees. The instruments used in this study were questionnaires and analyzed by using multiple regression. Based on the results of multiple regression analysis that the salary variable has a significant positive effect of 17.7%, on the performance of employees at PT. Plambo Pratama Joyo Santoso City of Tegal. If the employee's salary is increased, the effect on employee performance will also increase, the higher the employee's salary, the higher the employee's performance. The results of multiple regression analysis that the incentive variable has a significant positive effect of 46.8% on employee performance at PT. Plambo Pratama Joyo Santoso City of Tegal. Companies must increase incentives to employees so that employee performance can increase. This shows that incentives are highly expected by employees. F Test Results that salary variables and incentive variables together have a significant positive effect of 47.8% on employee performance at PT. Plambo Pratama Joyo Santoso City of Tegal. Companies must increase salaries and incentives to employees so that employee performance can increase. This shows that salaries and incentives are highly expected by employees. Based on the results of the analysis of this study, the authors suggest that companies increase salaries and incentives because they can influence the performance of employees of PT. Plambo Pratama Joyon Santoso. Keywords: Salary, Incentives and Performance